A case report of an aorto-pulmonary-venacaval fistula after penetrating cardiac injury. Issue 6 (15th December 2020) - Koen, Johannes Gerhardus; Wagenaar, Riegardt; Janson, Jacques T.
Abstract: Background: Penetrating cardiac injury (PCI) is an accepted burden in high violent crime areas. Traumatic intracardiac fistulae are however not that commonly detected on initial presentation, with most of these injuries being detected post-operatively or at routine follow-up. The literature is devoid of general principles around the pre-operative planning and intra-operative management in these cases, and thus warrant documented case reports by clinical units experienced in the management of these challenging clinical scenarios. Case summary: We describe a case report of a 29-year-old male patient presenting to our Cardiothoracic Unit with an aorto-pulmonary-venacaval fistula after a traumatic PCI. We describe the clinical presentation, diagnostic challenges, and institutional experience in the operative management of this case. Discussion: The patient was treated successfully with repair via sternotomy and femoral cardiopulmonary bypass with no neurological, pulmonary, or cardiac sequelae at early follow-up. The importance of selective pre-operative imaging in PCI, appropriate pre-operative surgical planning, and surgical experience in the management of these injuries is highlighted in this case presentation.